Description of the male of Tanyxiphium harriet (Hymenoptera: Mymaridae), with new distribution records and synonymy - Triapitsyn, Serguei V.; Aishan, Zhulidezi; Huber, John T. (Zootaxa, 2020)
Tanyxiphium longissimum Huber, syn. n. (Hymenoptera: Mymaridae) is synonymized under T. harriet (Zeya) based on examination of specimens from Hainan Island and Yunnan Province in the Oriental part of China, Sulawesi Island in Indonesia, Peninsular Malaysia, and Thailand. These are new country distribution records except for Thailand. The previously unknown male of T. harriet is described from Sulawesi Island, and the female is redescribed and illustrated based on non-type material examined.